Aрхітектурне проектування web систем - Койдан А.А. (ХНУРЕ, 2024)
The relevance of architectural design in integrated web systems is paramount in the rapidly evolving landscape of internet technologies. Ensuring high quality and efficient performance of web applications is crucial for success in competitive environments. This necessitates constant refinement and innovationIin architectural approaches to meet modern user demands. Architectural methodologies like ATAM and 4+1, alongside platforms like InsightQ, offer systematic analysis and optimization, balancing various system characteristics effectively. By amalgamating these methodologies and tools, developers aim to create highly efficient and quality web systems, aligning with user needs and contemporary market demands.
Keywords: Web системи; архітектурне проектування систем